Value Added Analysis of The Corn Supply Chain As Feed For Poultry In the Sub-District, Contact the City of BauBau - Haerunianti Haerunianti (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
This study aims to: (1) assess the performance trajectory of the corn supply chain for the needs of the animal feed industry. (2) analyze the added value of the animal feed maize marketing system. using the census sampling technique, where the entire population is sampled because the population is small or less than 35 respondents, so the sample in this study was 30 respondents, i.e. all actors in the chain of corn supply. The technique used to obtain both primary and secondary data in this study was carried out through face-to-face interviews using questionnaires. descriptively to answer the problems and objectives. At the same time, the added value in the animal feed maize marketing system uses the modified Hayami method which will be analyzed to address the second problem and research objective. The results showed that: (1) Supply chain performance consists of a single line, starting from corn collectors and selling to wholesalers. Then the feed company buys from wholesalers as the main supplier of corn. The results of animal feed will be sold to retailers and marketed by end consumers. (2) The value added process created in the animal feed sector which provides added value for corn is Rp. 7,500 per kg of animal feed and the profit earned in the company is Rp. 2,300, - per kg of feed, then the total profit for a month of production is Rp. 5,750,000.